Properties of Zc± (3900) produced in p p collisions PROPERTIES of Zc± (3900) ... ABAZOV et al. - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2019)
We study the production of the exotic charged charmoniumlike state Zc±(3900) in pp collisions through the sequential process ψ(4260)→Zc±(3900)π, Zc±(3900)→J/ψπ±. Using the subsample of candidates originating from semi-inclusive weak decays of b-flavored hadrons, we measure the invariant mass and natural width to be M=3902.6-5.0+5.2(stat)-1.4+3.3(syst) MeV and Γ=32-21+28(stat)-7+26(syst) MeV, respectively. We search for prompt production of the Zc±(3900) through the same sequential process. No significant signal is observed, and we set an upper limit of 0.70 at the 95% credibility level on the ratio of prompt production to the production via b-hadron decays. The study is based on 10.4 fb-1 of pp collision data collected by the D0 experiment at the Fermilab Tevatron collider.